A vivência do outro em Edmund Husserl - Claudia Coscarelli Salum (2011)
The conception of the self as freethought, typical of the modernity, presents a relationship between the self and the other in which the self is the one able to appropriate realitys mysteries or, still, the one able to interfere, to change and to create social realities. This new configuration of the relationship between the self and the other reveals to us, on one side, the subjects act empty of meaning, on the other side, the objectification of the lived experience of the other in the persons experience. This research has as its objective identifying how thelived experience of the other appears in the persons experience, through Edmund Husserls phenomenology. We adopted the lived experience of the other as a phenomenon to be researched in this work and we identified some reflections that propose new ways for thislived experience, from the intersubjectivity dimension. Investigating the Social Psychology field, we chose the Psychology of the Culture's perspective and the Phenomenology theory, as a theoretical reference essential to the study of this lived experience. We did a theoreticalresearch phenomenologically oriented, using two texts, chosen intentionally: Cartesian Meditations: An Introduction to Phenomenology and Ideas Pertaining to a Pure Phenomenology and to a fhenomenological Philosophy - First Book in which we noted thepossibility of a systematic reflection capable of leading us to the lived experience. Through ours analyzes, we reconstructed the way how the lived experience of the other appears, through the indications found in Husserls texts. We described the path of the lived experienceof the other in the subjects experience, showing fundamental elements to the comprehension of the way this experience occurs. In the dynamic, between the self and the other, we identified that to deep in the self perception coincides with the recognition of a constantopenness to the otherness and we defined four moments that this event happens, that are: the experience of the world, a question about the world, the meaning of the world and the value of the world. We entered the phenomenological field problematizing the theoretical differencesabout the theme of the lived experience of the other and we identified the specificity of Husserls analyzes when compared to others authors of the phenomenological field. We considered the relevance of knowing Husserls position, based in phenomenologys method,not only because of his pioneering theory, but to collect the intuitions followed by so many others philosophers. Still on that field, we could find some objections to the lived experience of the other in Husserls phenomenology philosophy of the sameness, idealism andsolipsism that contributed to the construction of a dialogue, through which we discussed some fundamental theoretical aspects to the comprehension of the theme of the other. Finally, we discussed the encounter with the lived experience of the other in the persons experience, so that we can be continually open, constantly elaborating the elements that are presented in this lived experience. We concluded our investigation recognizing that the comprehension of the process of double constitution between subjectivity and otherness contributes to thereflections about the possibilities of the lived experience of the other in the subjectivity field. We noted that in the encounter between the self and the other appears a joint value, lived in the act of realizing that our existence is in fact a shared existence. The interest in theaffirmation of this experience renews itself in every act of freedom, allowing us to desire a life directed by ethical criteria.